2011
DOI: 10.1103/physrevlett.106.161102
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Monopoles and Torqued Geometries in Gravity and Condensed Matter

Abstract: Torsional degrees of freedom play an important role in modern gravity theories as well as in condensed matter systems where they can be modeled by defects in solids. Here we isolate a class of torsion models that support torsion configurations with a localized, conserved charge that adopts integer values. The charge is topological in nature and the torsional configurations can be thought of as torsional 'monopole' solutions. We explore some of the properties of these configurations in gravity models with non-v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…This means that the torsion can stand in for the axial chemical potential. We can also study many other torsioninduced and dislocation-induced phenomena found in earlier works [2][3][4][5][6][7][19][20][21][22][23].…”
Section: Phenomenological Applicationmentioning
confidence: 77%
“…This means that the torsion can stand in for the axial chemical potential. We can also study many other torsioninduced and dislocation-induced phenomena found in earlier works [2][3][4][5][6][7][19][20][21][22][23].…”
Section: Phenomenological Applicationmentioning
confidence: 77%
“…One can approach this along the lines proposed in Randono & Hughes (2011). As a first step, we can replace the ansatz (3.1) by taking instead of (2.23) the orthogonal matrix that is a product of N factors The dot denotes the usual matrix product.…”
Section: Discussionmentioning
confidence: 99%
“…The geometric constraint (1.1) of the vanishing curvature rules out the disclinations. It was shown in Randono & Hughes (2011) that dislocations are also not relevant to the point-like soliton solutions. The solitons of this type are mentioned by Unzicker (2002), who calls them a 'Shankar monopole' (Shankar 1977) that describes a point-like defect in a A-phase superfluid Helium-3, (Mermin 1979;Vollhardt & Wölfle 1990;Volovik 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Real materials are imperfect and contain topological defects such as dislocations [15,18,35], disclinations [19,20] and gauge fields induced by strain [21,22]; therefore, a natural question is to formulate the physics of topological insulators in the presence of such defects [8]. These topological defects can be analyzed using the coordinate transformation method given in [26] which modifies the Hamiltonian for a topological insulator with a defect by the metric tensor and the spin connection [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we expect that the chiral excitations [29] will be sensitive to such defects. 3 In this paper, we will introduce the tangent space approach used in differential geometry [24,33,34] to study the propagation of electrons for a space-dependent coordinate [26]. We find that the continuum representation of the edge dislocation [26] generates a spin connection [30][31][32] which is controlled by the Burger vector.…”
Section: Introductionmentioning
confidence: 99%